Pelatihan Perangkat Lunak Matlab Pada Sistem Tenaga Listrik Bagi Mahasiswa Institut Teknologi Adhi Tama Surabaya - Wardani, Ayusta Lukita; Widyartono, Mahendra; Aribowo, Widi; Rahmadian, Reza; Hermawan, Aditya Chandra; Laksmi, Nur Vidia (JPP IPTEK (Jurnal Pengabdian dan Penerapan IPTEK), 2024)
The use of software developed by The MathWorks is increasingly massive due to its ease of operation. Matlab software can make it easier to optimize and also model a system design so that engineering students, especially Electrical Engineering, need to be equipped with the knowledge and skills to solve Electrical Power System problems. So in this activity, training was carried out in using the software, starting from running Matlab Online, creating code such as basic calculation operations, forming matrices, plotting data and using Simulink which contains a collection of block diagrams. The level of success of this training is measured through two indicators. And it can be concluded that there is an increase in knowledge and skills through comparing the Pre-Test and Post-Test Scores as well as analysis of the Paired Sample T Test using Ms. Excell